Hubungan Minat Baca dengan Hasil Belajar IPS di Sekolah Dasar - Dania, Nilma; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This study aims to determine whether or not there is a relationship between reading interest and learning outcomes in social studies learning. This type of research is correlational. The population in this study were all fifth grade students of SD Negeri Gugus 3 Kecamatan Bonjol. This study uses Total Sampling with a total sample of 35 students. The instruments of data colletion used is questionnaire. The data analysis technique used by SPSS v16. Computer data analysis techniques consisted of instrument testing, analysis prerequisite test (normality test, linearity test, and hypothesis test).From the data analysis performed the Pearson Correlation value is 0.650 and r table is 0.344 with a significance level of 5%. The results of the calculation show that r count 0.650 > r table 0.344. The significance value obtained is 0,000 < 0,05. It can be concluded that reading interest has a strong / high relationship with social studies learning outcomes of fifth grade students of SD Negeri Gugus 3 Kecamatan Bonjol. Keywords: reading interest, learning outcomes, social studies.